Political Dynasty Formation and Democratic Consolidation in West Java: A Comparative Study of Banten, Tasikmalaya, and Cirebon - Sri Dewi Miladiyah (Politeknik Siber Cerdika Internasional, 2025)
Political dynasties in Indonesia have significantly influenced the consolidation of democracy, particularly in the context of decentralization. This study examines the formation and impact of political dynasties in three regions of West Java: Banten, Tasikmalaya, and Cirebon, from 2005 to 2024. The research aims to understand how dynastic politics has shaped democratic quality indicators such as electoral competitiveness, institutional accountability, and civil liberties. A qualitative comparative case study approach was employed, combining process tracing and structured focused comparison. Key findings reveal that while political dynasties have systematically reduced electoral competition, they have also led to varying outcomes in democratic consolidation. Banten’s dynastic collapse resulted in democratic recovery, while Cirebon’s consolidating dynasty and Tasikmalaya’s traditional elite system showed differing levels of democratic erosion. The study highlights the role of external accountability mechanisms, particularly national anti-corruption agencies, in curbing dynastic power. It concludes that strengthening local democratic institutions, improving electoral system competitiveness, and fostering civil society are crucial for mitigating the negative effects of political dynasties on democratic consolidation. The research contributes to a deeper understanding of the relationship between political dynasties and democratic governance in decentralized systems. These findings have critical policy implications for democratic reform initiatives in Indonesia and other decentralized democracies, emphasizing the need for multi-level governance frameworks that balance local autonomy with robust accountability mechanisms.